Peran Lingkungan Persaingan di Perusahaan Freight Forwarder - Arum Anggorowati; Sarinah Sihombing; Nofrisel Nofrisel (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
The purpose of the paper is to find out the effect of the sea freight forwarding companies to the marketing performance by moderating the role of the competitive environment in the freight forwarder’s companies. The paper used survey method by giving questionnaire to 86 samples taken randomly. The analysis method used MRA (moderated regression analysis). The results of the paper show that there is positive and significant direct effect of the sea freight forwarding to the marketing performance by moderating the competitive environment however, there is also the negative effect